Problem Based Learning in Foreign Language Learner’s (FLL) Grammar Class: How Will Students Perceive It? - Ayuni, Marlinda; Susanti, Novia Indri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Grammar is one of the subjects that should be learnt at English Department, but most of them assume that grammar is very difficult. The purposes of this research is to know that Problem Based Learning is the method that can improve student’s grammar competence and make sure that Problem Based Learning make students improve their grammar competence. Is Problem Based Learning effective to teach grammar for FLL? To describe this perception this study uses qualitative research with questionnaire and interview. This research is supported by FLL from students of state university in Magelang. The result shows that students of English department as foreign language learner difficult to understand grammar. Some differences come when they use problem based learning. Problem based learning is one of the methods that can help student to overcome grammar problem.